(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the development of international cooperation in Uzbekistan’s silk industry from 2000 to 2021 and evaluates its economic significance. Special attention is given to institutional reforms, the introduction of the cluster system, and the attraction of foreign investment after 2017. Strategic partnerships with countries such as China and Azerbaijan have contributed to increased production, expanded export potential, and higher employment in rural areas. The study justifies the importance of adopting international experience, introducing technological innovations, and enhancing regional integration to improve the competitiveness of the silk sector.